Manejo de inventarios en la “despensa Olaya” en los años 2020 – 2021 - Vera Carrasco, Byron Adolfo (2022)
Inventory control in large companies, as well as in small businesses that exist today, plays an important role in their profitability. Well, it is known that a company or business that properly manages its assets has a greater chance of being able to reduce its risks of economic loss and, in turn, has the opportunity to increase the profits obtained at the end of the accounting period. For many of the business owners, the fact of carrying out an adequate inventory control becomes complicated, due to the lack of knowledge of how to use the applicable methods for the purpose. What makes it impossible for inventory management to be the most appropriate, weakening the strengths of the business, significantly reducing the income generated by sales. It is for this reason that most of these businesses do not take full advantage of the available assets, which is a factor that weakens their economic health. For which, carrying out the correct control or management of inventories is of vital importance, since it is one of the key factors that directly affects the mission, as well as the vision that has been established in any type of business can be met, in addition to the fact that resources can be optimized allowing the desired success to be achieved.